Systemic therapies for metastatic hormone-sensitive prostate cancer: network meta-analysis - Mori, Keiichiro; Mostafaei, Hadi; Sari Motlagh, Reza; Pradere, Benjamin; Quhal, Fahad; Laukhtina, Ekaterina; Schuettfort, Victor M; Kramer, Gero; Abufaraj, Mohammad; Karakiewicz, Pierre I; Kimura, Takahiro; Egawa, Shin; et al. (BJU international, 2022)
OBJECTIVES: To perform a systematic review and network meta-analysis to compare the efficacy and safety of currently available treatments for the management of metastatic hormone-sensitive prostate cancer (mHSPC), as there has been a paradigm shift with the use of next-generation androgen receptor inhibitors (ARIs) and docetaxel. METHODS: Multiple databases were searched for articles published before May 2020 according to the Preferred Reporting Items for Systematic Review and Meta-analysis extension statement for network meta-analysis. Studies comparing overall/progression-free survival (OS/PFS) and/or adverse events (AEs) in patients with mHSPC were eligible. RESULTS: Nine studies (N = 9960) were selected, and formal network meta-analyses were conducted. Abiraterone (hazard ratio [HR] 0.83, 95% credible interval [CrI] 0.76-0.90), docetaxel (HR 0.90, 95% CrI 0.82-0.98), and enzalutamide (HR 0.85, 95% CrI 0.73-0.99) were associated with significantly better OS than androgen-deprivation therapy (ADT), and abiraterone emerged as the best option. Abiraterone (HR 0.71, 95% CrI 0.67-0.76), apalutamide (HR 0.73, 95% CrI 0.65-0.81), docetaxel (HR 0.84, 95% CrI 0.78-0.90), and enzalutamide (HR 0.67, 95% CrI 0.63-0.71) were associated with significantly better PFS than ADT, and enzalutamide emerged as the best option. Abiraterone (HR 0.85, 95% CrI 0.78-0.93), apalutamide (HR 0.87, 95% CrI 0.77-0.98), and enzalutamide (HR 0.80, 95% CrI 0.73-0.88) were significantly more effective than docetaxel. Regarding AEs, apalutamide was the likely best option among the three ARIs. In patients with low-volume mHSPC, enzalutamide was the best option in terms of OS and PFS. CONCLUSIONS: All three ARIs are effective therapies for mHSPC; apalutamide was the best tolerated. All three seemed more effective than docetaxel. These findings may facilitate individualised treatment strategies and inform future comparative trials.
Keywords: #ProstateCancer; docetaxel; hormony; Male; antagonisté androgenních receptorů; Prostatic Neoplasms; mužské pohlaví; #PCSM; antagonisté androgenů; Androgen Antagonists; Hormones; lidé; androgen receptor inhibitors; Humans; nádory prostaty; Androgen Receptor Antagonists; metastatic hormone-sensitive prostate cancer; Docetaxel; network meta-analysis